NEW FACE OF RELIGIOUS AFFAIR MINISTER AND THE EPISTEMOLOGY OF QUR’ANIC ETHICS: A SYNCHRONIC-DIACHRONIC READING ON QS. AL-HUJURĀT (49): 11-13 - Egi Tanadi Taufik (Universitas Islam Negeri Ar-Raniry, 2021)
Aesthetic phenomenon that is happening in Indonesia is suspected by the election year. Debates between presidents that contain